2021
DOI: 10.3389/fmicb.2021.777817
|View full text |Cite
|
Sign up to set email alerts
|

Long-Read Sequencing Reveals Evolution and Acquisition of Antimicrobial Resistance and Virulence Genes in Salmonella enterica

Abstract: Salmonella enterica is a significant and phylogenetically diverse zoonotic pathogen. To understand its genomic heterogeneity and antimicrobial resistance, we performed long-read sequencing on Salmonella isolated from retail meats and food animals. A collection of 134 multidrug-resistant isolates belonging to 33 serotypes were subjected to PacBio sequencing. One major locus of diversity among these isolates was the presence and orientation of Salmonella pathogenic islands (SPI), which varied across different se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…However, there was also considerable variation, as shown by their comparison with some key examples ( Figure 1 ), which include the original pESI plasmid, detected in a human isolate from Israel (119944), which lacks most of the R1 region [ 7 , 8 ]. A higher degree of similarity was found with two bla CTX-M-65 -positive plasmids, with or without fosA3 (FSIS1502169 and CVM N18S2198, respectively; [ 14 , 24 ]), identified in isolates from chicken samples in the USA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was also considerable variation, as shown by their comparison with some key examples ( Figure 1 ), which include the original pESI plasmid, detected in a human isolate from Israel (119944), which lacks most of the R1 region [ 7 , 8 ]. A higher degree of similarity was found with two bla CTX-M-65 -positive plasmids, with or without fosA3 (FSIS1502169 and CVM N18S2198, respectively; [ 14 , 24 ]), identified in isolates from chicken samples in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…Infantis ([ 13 , 16 ]; Figure 2 ). They have been reported in humans and along the poultry production chain in the USA and South America, with only a limited number of isolates being detected in other livestock animals [ 14 , 24 , 42 , 43 , 44 , 45 , 46 ]. Isolates carrying pESI-like plasmids positive for bla CTX-M-65 ± fosA3 have also been associated with human clinical cases in Europe, specifically in patients with a travel history to America [ 10 , 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the genomic regions of A. cerana symbionts were essentially identical to two plasmids belonging to the IncQ-1 subgroup. This finding indicates that the IncQ plasmids are integrated into the chromosome of bee gut bacteria, as found in Salmonella enterica [ 47 ] and Vibrio cholerae [ 48 ]. Interestingly, we detected sequence deletions in the integrated plasmid fragments, especially in the strB and replicon modules.…”
Section: Discussionmentioning
confidence: 99%
“…Clade 2 primarily contained human isolates, and its pangenome was considerably smaller than those of the other clades, but further analysis to understand these differences was not performed ( 2 ). Closed sequences of Reading are required for pangenome exploration and to further understand the novel “emergent” subclade, but only 11 are currently available ( 3 , 4 ), and none are from US patients. Here, we generated five complete clinical Reading sequences from Clades 1 and 2 to serve as references.…”
Section: Announcementmentioning
confidence: 99%